Criminal Liability for Infanticide Committed by the Biological Mother in Palangka Raya City - Sulistia Sulistia; Rollys Suriani; Claudia Yuni Pramita; Aristoteles Aristoteles (Fakultas Syariah IAIN Langsa, 2026)
This study examines the criminal responsibility of biological mothers who commit infanticide in Palangka Raya City by analyzing the legal framework, judicial practice, and the socio-psychological conditions surrounding such cases. Using a normative juridical method complemented by case-based analysis, the research explores how Indonesian criminal law—particularly Articles 341–343 of the Criminal Code—constructs liability for mothers who kill their newborn infants under circumstances of psychological pressure, social stigma, or extramarital pregnancy. Findings indicate that while the law provides specific provisions allowing for reduced sentencing based on maternal mental disturbance or societal coercion, judicial decisions in Palangka Raya still emphasize the need to balance compassion with deterrence. The study concludes that criminal responsibility must be viewed not only through the lens of legal doctrine but also through an understanding of maternal vulnerability, social exclusion, and the need for stronger preventive mechanisms, including reproductive education and supportive social services.